Environmental winds : making the global in southwest China - Hathaway, Michael J. (University of California Press, 2013)
"The book challenges the notion that globalized social formations emerged solely in the Global North prior to impacting the Global South. Instead, such formations have been constituted, transformed, and propelled through diverse, site-specific social interactions that complicate and defy divisions between 'global' and 'local.' The book brings the reader into the lives of Chinese scientists, officials, villagers, and expatriate conservationists who were caught up in environmental trends over the past 25 years. Hathaway reveals how global environmentalism has been enacted and altered in China, often with unanticipated effects, such as the rise of Indigenous rights, or the reconfiguration of human/animal relationships, fostering what rural villagers refer to as "the revenge of wild elephants.""--